Pengaruh Lingkungan Fisik Dan Hedonic Shopping Value Terhadap Pembelian Tidak Direncanakan Di Giant Express Cilegon - Muhamad Suhaemi; Juliandra Muharram (Jurnal Manajemen, 2018)
This study aims to determine the effect service scape on impulse buying, to determine the effect hedonic shoping value on impulse buying , and to determine the effect service scape and hedonic shoping value on impulse buying at giant express Cilegon.This study uses quantitative research methode population in this study is consumerswho have shoped at giant express cilegon data were analyzed with SPSS version 20. The methode of selecting type of sample used accidental sampling. Data was done collection by spreading questionnaires to 100 respondents.While based on simultant test with f test results showed that variables of servicescape and hedonic shoping value simultaneously significant effect on impulse buying. Based on partial test with t test showed that variables of service scape effect the significance of the impulse buying  with a significance level of 0,000. And hedonic shoping value has significane effect of the impulse buying with a significant level of 0,000.Keyword : Servicscape, Hedonic Shopping Value, Impulse Buying